2015
DOI: 10.1364/ao.54.000728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil temperature on optical frequency transfer through unidirectional dense-wavelength-division-multiplexing fiber-optic links

Abstract: Results of optical frequency transfer over a carrier-grade dense-wavelength-division-multiplexing (DWDM) optical fibre network are presented. The relation between soil temperature changes on a buried optical fibre and frequency changes of an optical carrier through the fibre is modelled. Soil temperatures, measured at various depths by the Royal Netherlands Meteorology Institute (KNMI) are compared with observed frequency variations through this model. A comparison of a nine-day record of optical frequency mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…A fiber-based femtosecond frequency comb (Menlo Systems FC1500) is used to measure the frequency of the light at wavelengths λ 1 and λ 2 (see Fig 3). Its long term stability is provided by a GPS disciplined rubidium clock (FS 725) with an intrinsic frequency stability of 10 −11 in 1 s integration time and 10 −12 in 10 000 s. This clock also serves as long term reference for all rf frequencies in the experiment and its stability has been verified to ∆ν/ν ≈ 10 −11 via an optical fiber network [13].…”
mentioning
confidence: 99%
“…A fiber-based femtosecond frequency comb (Menlo Systems FC1500) is used to measure the frequency of the light at wavelengths λ 1 and λ 2 (see Fig 3). Its long term stability is provided by a GPS disciplined rubidium clock (FS 725) with an intrinsic frequency stability of 10 −11 in 1 s integration time and 10 −12 in 10 000 s. This clock also serves as long term reference for all rf frequencies in the experiment and its stability has been verified to ∆ν/ν ≈ 10 −11 via an optical fiber network [13].…”
mentioning
confidence: 99%
“…Distributed Temperature Sensing (DTS) technique for testing the inside of fibre cable cores and use of weather stations to test the outside temperatures in aerial cables have both revealed that either approach is reliable in analyzing the impact of temperature on PMD in fibre cables [1,2,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For buried cables, algorithms have been applied on metrological weather data to determine temperature at the depth where the cable is buried [7]. This method has been used to analyze frequency-shifts and chromatic dispersion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On links with phase-coherent amplification, 10 −20 fractional frequency uncertainty has been demonstrated, so fiber links do not limit the clock signal uncertainty. Efforts are underway to establish a network of fiber connection between European research institutes, including preliminary work on a 298 km link in the Netherlands between Amsterdam and Groningen [77].…”
Section: Optical Fiber Networkmentioning
confidence: 99%
“…4.3). Its long term stability is provided by a gps-disciplined rubidium clock (SRS fs ) with an intrinsic frequency stability of 10 −11 in 1 s integration time and 10 −12 in 10 000 s. This clock also serves as long term reference for all rf frequencies in the experiment and its stability has been verified to ∆ν/ν ≈ 10 −11 via an optical fiber network [77].…”
Section: Determination Of Optical Frequenciesmentioning
confidence: 99%